2021
DOI: 10.1017/wsc.2021.33
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of imidazolinone-resistant weedy rice in Malaysia: the current status

Abstract: Weedy rice (Oryza sativa f. spontanea or O. sativa complex) has become a severe threat to Malaysian rice (Oryza sativa L.) granaries after the direct-seeding method of rice cultivation was introduced in the late 1980s. Since then, researchers have studied the biology and ecology of weedy rice, and espoused the evolutionary theory of the origin of Malaysian weedy rice. This review paper aimed to synthesize the body of knowledge about weedy rice and the evolution of herbicide-resistant weedy rice in Malaysia. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The cycle consists of three growth stages: (1) vegetative (1-41 days after planting), (2) reproductive (42-77 days), and (3) maturative (83-99 days). To boost rice production, Malaysia's government introduced a rice granary, arable land, with a centralised canal irrigation system that the federal government administrates (Ruzmi et al, 2021). To date, 12 rice granaries have been developed that cover a total area of 425,613 hectares.…”
Section: Rice Cultivation In Malaysia and The Weed Predicamentmentioning
confidence: 99%
See 1 more Smart Citation
“…The cycle consists of three growth stages: (1) vegetative (1-41 days after planting), (2) reproductive (42-77 days), and (3) maturative (83-99 days). To boost rice production, Malaysia's government introduced a rice granary, arable land, with a centralised canal irrigation system that the federal government administrates (Ruzmi et al, 2021). To date, 12 rice granaries have been developed that cover a total area of 425,613 hectares.…”
Section: Rice Cultivation In Malaysia and The Weed Predicamentmentioning
confidence: 99%
“…It has also been reported that DSR experienced a 7-10 days early maturity (Nagargade et al, 2018). DSR has been adopted in Malaysia since the late 1980s (Ruzmi et al, 2021). In Asia, DSR is practised in 21% or 29 million hectares of the total cultivated area (Alam et al, 2020).…”
Section: Rice Cultivation In Malaysia and The Weed Predicamentmentioning
confidence: 99%
“…Third, and more important, is the evolution of IMI-resistant weedy rice populations. After 3 years of Clearfield rice cultivation, weedy rice hybrids with several trait modifications appeared in rice fields, in the USA (Louisiana and Arkansas), Brazil [38], Colombia, Costa Rica, Italy ([37]: table 3), and in Malaysia [39][40][41]. In Arkansas for instance, 10-60% of these hybrids were found to be herbicide-resistant [42].…”
Section: Herbicide (Imi)-resistant Rice Varieties: Low Efficiency and Sustainabilitymentioning
confidence: 99%
“…On the one hand, monoculture requires less farm implements, knowledge, and practical experience and so is simpler than crop rotation. Moreover, some countries, e.g., Malaysia, are not selfsufficient in rice production; then, arable lands are reserved by the government and monocropped with rice to ensure food security [41]. On the other hand, the impacts of crop rotation on economic returns are not clearly established.…”
Section: Complexity and Uncertain Profitabilitymentioning
confidence: 99%
“…The gap was substituted with imports from mostly Association of Southeast Asian Nations (ASEAN) countries. The current production of rice is 2.91 million tons, however, the country still imports about 20-24 percent of its rice demand [2,3] with an average consumption of 82 kg per capita per year [4]. Malaysia's rice venture is too expensive, and the country would need not grow any rice at all if looking from an economic viewpoint such as comparative advantage in relation to the world market.…”
Section: Introductionmentioning
confidence: 99%